The Third Sex: Historians, Consumer Society, and the Idea of the American Consumer - Restad, Penne (Journal of Social History, 2014)
Scholars have profiled the American "consumer" in myriad ways, among them: self determining, self-destroying, morally decayed and hedonistic, gendered, "the public," and as simple economic functionary. During the nineteenth century, Americans, influenced by republican ideals and religious ambivalence about the marketplace, did not appreciably modify long-standing associations of "consumer" with waste. Yet the imperatives of an increasingly important commercial sphere, while not significantly eroding the word's taint, complicated its meaning. Economists and sociologists in particular sought to describe the ways in which consumers and consumerism altered American life. It was not until the mid-twentieth century that historians began to take notice. At first, the role of advertising served as their central analytical tool but, as the field of consumer history matured from the late 1960s and into the 1990s, approaches framed by other disciplines informed American historians 7 explications of what had by then clearly emerged as a consumption-centered society. Notably, an uneasiness with the moral implications of consumer behavior continued to thread through scholarly work. This article considers the ways that cultural preconceptions consciously or unconsciouly have shaped our ability to imagine and evaluate "the consumer." It concludes that such an entity may be best understood as a highly malleable, often disruptive "other" that animates a scholarship seeking to understand its dimensions, but it bears little simito a real being.
Keywords: Business History and gender